The Influence of Production Factors, Prices, and Macroeconomic Conditions on Timor-Leste's Coffee Export Volume - Mariela Seixas Miranda; Agnes Quartina Pudjiastuti; Cakti Indra Gunawan (IRDH International Journal of Social Sciences & Humanities, 2026)
Coffee is one of Timor-Leste’s leading export commodities, playing a crucial role in foreign exchange earnings and rural livelihoods. However, the performance of coffee exports has shown considerable fluctuations over time. This study aims to examine the effects of export coffee prices, domestic coffee production, domestic coffee prices, coffee plantation area, inflation, and per capita coffee consumption on the volume of coffee exports in Timor-Leste during the period 2002–2024.  This research employs time series secondary data obtained from UN Comtrade, the World Bank, the International Coffee Organization, and national statistical sources. The analytical method used is multiple linear regression estimated using the Ordinary Least Squares (OLS) approach.  The results indicate that all independent variables jointly have a significant effect on coffee export volume. Partially, export coffee prices, domestic coffee production, coffee plantation area, and per capita coffee consumption have a positive and significant effect on coffee export volume. Meanwhile, domestic coffee prices and inflation do not show a significant effect. These findings suggest that Timor-Leste’s coffee export performance is more strongly influenced by international market factors and production capacity than by domestic macroeconomic conditions. Therefore, policies aimed at increasing coffee exports should focus on strengthening production capacity, expanding plantation areas, and enhancing the competitiveness of Timor-Leste coffee in global markets